2014
DOI: 10.4081/aiua.2014.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis in Italy: An epidemiological study

Abstract: Results: In Italy prevalence of urolithiasis in 2012 was 4.14%, it was higher in males than in females (4.53% versus 3.78%) with a positive relation with increasing age. The highest prevalence rate of urolithiasis was reported in the region Campania (6.08%). The general incidence was 2.23 *1000, with the highest incidence in the region Sicilia (3.15 *1000). Incidence was higher in group age 65-74 years (3.18 *1000). Conclusions: In Italy the incidence and prevalence of urolithiasis is increasing with particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
1
26
0
4
Order By: Relevance
“…The management of patients with UUT stones and selection of surgical options differ between different countries, despite comparable economic status due to national specificities in terms of healthcare politics and financial incentives . Overall, surgical options are on the rise all over the Western Hemisphere . Medical expulsive therapy for ureteric calculi has been widely discussed and prescribed for years but recent data from a large randomised controlled clinical trial suggests it is ineffective .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of patients with UUT stones and selection of surgical options differ between different countries, despite comparable economic status due to national specificities in terms of healthcare politics and financial incentives . Overall, surgical options are on the rise all over the Western Hemisphere . Medical expulsive therapy for ureteric calculi has been widely discussed and prescribed for years but recent data from a large randomised controlled clinical trial suggests it is ineffective .…”
Section: Discussionmentioning
confidence: 99%
“…Global literature reports an increasing prevalence of urinary stone disease . Continued improvements in technology (flexible ureteroscopes, lasers, ultrasonic and pneumatic lithotripsy and refined shockwave lithotripsy [SWL]) have made the treatments more effective, fast, and comfortable for both patients and medical professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of treatment options and surgical options for patients with urinary stones also depends on the healthcare policy and healthcare insurance finances of individual countries . Recent reports from Western countries suggest that the overall choice of minimally invasive surgical procedures is increasing as a primary treatment for urinary tract stone . In the present study, the use of SWL for treating USD increased by 16% from 89 553 in 2009 to 104 013 in 2016.…”
Section: Discussionmentioning
confidence: 66%
“…10 Recent reports from Western countries suggest that the overall choice of minimally invasive surgical procedures is increasing as a primary treatment for urinary tract stone. 2,[11][12][13][14][15][16][17] In the present study, the use of SWL for treating USD increased by 16% from 89 553 in 2009 to 104 013 in 2016. The reason for the high rate of SWL in the primary treatment of USD in Korea is presumably because of the large number of SWL carried out at local medical clinics.…”
Section: Discussionmentioning
confidence: 74%
“…They indicated that the risk of nephrolithiasis in age group of 14 to 18 years is 10 times greater. The hospitalization rate also follows the same pattern (9,12,21,22). In a Tasian study, the greatest change belonged to 15 to 19 year olds, and the incidence of nephrolithiasis increased by 26% per five years.…”
Section: Incidence and Trendmentioning
confidence: 74%